The THE BELIEFS OF HEALTH SEEKING BEHAVIOR FISHERMEN IN COASTAL PUGER JEMBER REGENCY: - - Tania Hesti Novitasari; Mury Ririanty; Iken Nafikadini (International Journal of Islamic and Complementary Medicine, 2023)
The high health risks of working as fishermen increase the potential for health seeking behavior of fishermen. Health seeking behavior is also applied by the Puger community, which is a southern coastal area in Jember Regency, although based on a preliminary study not a few of them ignore their health problems. This type of research is a quantitative research with a cross sectional approach. A sample of 110 respondents was taken by simple random sampling from a population of 5247 fishermen and domiciled in Mandaran Hamlet and Krajan Hamlet, Puger Wetan Village, Puger District, Jember Regency. The resulting data were tested using logistic regression. The result showed that trust has a significant effect with p <α value of 0.000 <0.05. Someone who has a belief in modern medicine tends to have a 21.333 greater influence in determining treatment seeking behavior compared to respondents who have a belief in traditional medicine. Suggestions need to be explored more deeply in each type of belief in fisherman's health seeking behavior using qualitative methods.and health promotion on safe treatment seeking behavior for fisherman's health.